Analisis Kemampuan Berpikir Kritis Matematika Materi Perkalian Peserta Didik Kelas IV SDN Kestalan No. 05 Surakarta - Novalia Yudha Aji Pamungkas; Anita Trisiana; Ema Butsi Prihastari (Journal on Education, 2023)
The purpose of this research is to know students' critical thinking skills, to know the supporting factors and inhibiting factors, and to find out the teacher's solutions in overcoming the barriers to students' critical thinking abilities in learning mathematics to improve Class IV material at SDN Kestalan No. 05 Surakarta. The research subjects were the principai, class IV teacher and 3 class IV students. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used in this study is descriptive qualitative with an interactive model. The results of the study show that 1) Critical thinking skills in high category students can respond to questions quickly, precisely and can provide conclusions. Medium category students can answer questions but still need guidance in making conclusions. The critical thinking ability of low category students never answers questions that have been given by the teacher, and rarely asks. 2) supporting factors, namely the motivation that has been given by the teacher and the interaction of teachers and students. 3) inhibiting factors, namely the role of parents in motivating students, the ability to count students in class IV, and infrastructure 4) The teacher's solution is to implement reading literacy in class, provide critical thinking exercises in every daily test, communicate between teachers and parents, and increase the hours to 0 (Zero) for students who have low abilities.